The Impact of Problem-Based Learning on Students' Problem-Solving Skills and Learning Motivation: A Perspective on Learning Styles - Muhammad Akbar Chaniago; Retno Arianingrum; Muhammad Habib Ash Shiddiqi (Jurnal Penelitian Pendidikan IPA, 2025)
Problem-solving ability and learning motivation are essential in chemistry learning, yet often overlooked in conventional instruction. This study investigates the effects of problem-based learning (PBL) versus discovery learning on students’ problem-solving ability and motivation, while also examining the influence of learning styles. Using a quasi-experimental pretest-posttest control group design, XI MIPA students at SMA Negeri 9 Bengkulu City were assigned to either a PBL or discovery learning group. Data were collected through tests, questionnaires, and learning style inventories, and analyzed using MANOVA. Results indicated no significant difference between the two models in improving problem-solving ability or motivation. However, learning styles significantly affected both outcomes, with visual, auditory, and kinesthetic learners performing differently. PBL contributed modestly to both variables (2.4% for problem-solving, 0.4% for motivation), and no interaction effect with learning styles was found. These findings highlight the need to align teaching strategies with students' learning styles to support more effective learning. The study offers practical implications for fostering adaptive instruction in chemistry classrooms and enhancing scientific literacy.